Corak Tasawuf Al-Ghazali dan Relevansinya dalam Konteks Sekarang - Abd. Moqsith Ghazali (AL-TAHRIR, 2013)
Abstracts: Al-Ghaza>li’s < sufism –which described as more khuluqi-'amali in character- becomes the creed of majority of Muslims in the world, in fact adhered by some sects within Judaism and Christianity. Although some Muslim thinkers, such as Ibn Rushd, criticized al-Ghaza>li<, but his arguments in Ih}ya>’ ‘Ulum al-Di>n seem to be too solid to tear down. This article tries to explore the main points of al-Ghaza> li<’s thoughts in the atmosphere of contemporary world and came to conclusion that in this time when Islam is often expressed in harsh and barren manners, al-Ghaza>li’s sufism shows its relevance and significance. He offers the concept of love of God(mah}abbah), oneness of God (tawh}id), fear of God (makha>fah ), and gnosis (ma’rifah) to the mankind. According to al-Ghaza>li , someone who loves God must love God's creatures as well. This concept leads to the good behaviors such as desire to unite oneself with God by repentance (tawbah), asceticism (zuhd) for fear of being far from God, trusting in God (tawakkul), and being pleased with all decisions and provisions of God (rid}a). These spiritual stages will lead to the degree of knowing God (ma'rifah). Modern society, that often feel alienated, will find the book Ih}ya> 'Ulu> m al-Di>n as a cooling oasis.